Introduksi Model Perencanaan Pelatihan Grant Writing Skill Bagi Tenaga Harian Lepas – Tenaga Bantu (THL-TB) Penyuluh Pertanian Kabupaten Jember - Najmah Faizah (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2018)
The developing of agriculture has many supports from both government and non-government institutions, implementing in the form of grants/assistance/loan to farmers. There are many types grants can be accessed by farmers on the condition of submitting proposals. On the other hand, farmers with a majority of low-educated people find it difficult to perform. As a extension agent, the contract officer  (THL-TB) of agricultural extension agents have obligation to provide assistance to the farmers. Unfortunately, they have limitation capacity and access to develop self-capacity cause the number THL-TB of agricultural extension agents have limitation experiences. This study has aims to determine the characteristics of THL-TB of agricultural extension agent in Jember Regency and to analyze the introduction of training plan model of grant writing skill for THL-TB agricultural extension agent in Jember Regency. The analysis method is descriptive analysis and training plan model of Goad. The target of training participants are 48 THL-TB agricultural extension agents in Jember Regency who  under  40  years  old  with  highest  education  (D3  and  bachelor  degree  I). Introducing training plans uses the basis of the Pimentel and Franco approache consist of 3 elements, they are pre-implementation, implementation and post-implementation.